2012
DOI: 10.1016/j.cell.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

p53 Opens the Mitochondrial Permeability Transition Pore to Trigger Necrosis

Abstract: Summary Ischemia-associated oxidative damage leading to necrosis is a major cause of catastrophic tissue loss in human health. Elucidating its signaling mechanism is of paramount importance. p53 is a central stress sensor responding to multiple insults including oxidative stress to orchestrate apoptotic and autophagic types of cell death. Whether p53 can also activate oxidative stress-induced necrosis is unknown. Here we uncover a role of p53 in activating necrosis. In response to oxidative stress, p53 accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
628
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(670 citation statements)
references
References 43 publications
26
628
2
7
Order By: Relevance
“…p53 directly interacts with multidomain proteins of the Bcl‐2 family at the mitochondrial outer membrane and induces mitochondrial outer membrane permeabilization, which is a prominent apoptotic checkpoint (Mihara et al ., 2003; Tomita et al ., 2006; Follis et al ., 2014). Several stresses such as hypoxia and ischemia induce translocation of p53 protein to mitochondria (Sansome et al ., 2001; Erster & Moll, 2004; Vaseva et al ., 2012). Mitochondrially targeted p53 leads to cell death in solid tumor models (Palacios et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 directly interacts with multidomain proteins of the Bcl‐2 family at the mitochondrial outer membrane and induces mitochondrial outer membrane permeabilization, which is a prominent apoptotic checkpoint (Mihara et al ., 2003; Tomita et al ., 2006; Follis et al ., 2014). Several stresses such as hypoxia and ischemia induce translocation of p53 protein to mitochondria (Sansome et al ., 2001; Erster & Moll, 2004; Vaseva et al ., 2012). Mitochondrially targeted p53 leads to cell death in solid tumor models (Palacios et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, p53 physically interacts with cyclophilin D (CypD) and the p53‐CypD complex results in mitochondrial permeability transition pore opening and mediates cell death caused by ischemic injury. Cyclosporine A pretreatment or reduction of p53 proteins prevents formation of the p53‐CypD complex in an ischemic injury mouse model (Vaseva et al ., 2012). In the current study, we found that SIRT3 rescues mito‐p53‐induced cytochrome c release in primary neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In response to oxidative stress, p53 accumulates in the mitochondrial matrix where it forms a complex with CypD and triggers mPTP opening (Vaseva et al., 2012). Recently, Lebedev et al.…”
Section: Putative Molecular Components Of Mptp and Agingmentioning
confidence: 99%
“…Although p53 is involved in multiple cellular processes, including growth arrest, DNA damage repair, apoptosis, senescence 38 and, by more recent evidence, also necrosis and autophagy, 39,40 we have no clear understanding of which process is responsible for tumour suppression or chemotoxic cell death. In addition to apoptosis, experimental evidence has favoured senescence as a p53-induced anti-tumour response, 41 whereas others, 42 using different models, reported p53-induced senescence to hamper DNA response by blocking apoptosis.…”
Section: Tp53mentioning
confidence: 99%